2021
DOI: 10.1002/cssc.202100854
|View full text |Cite
|
Sign up to set email alerts
|

Platinized Titanium as Alternative Cost‐Effective Anode for Efficient Kolbe Electrolysis in Aqueous Electrolyte Solutions

Abstract: Five commercial materials were assessed for electrochemical conversion of n‐hexanoic acid by Kolbe electrolysis. Platinized titanium performed best, achieving a coulombic efficiency (CE) of 93.1±6.7 % (n=6) for the degradation of n‐hexanoic acid and 48.3±3.2 % (n=6) for the production of n‐decane, which is close to the performance of pure platinum (89.7±14.4 and 55.5±3.5 %; n=6). 56.7 mL liquid fuel was produced per mole n‐hexanoic acid, converting to an energy demand of 6.66 kWh and 1.22 € per L. Using optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…It was shown that at extreme cell voltages above 20 V a yield of 64.7 % of n‐triacontane was obtained in a basic electrolyte (1.3 M KOH) and at a cell temperature of 55 °C. Besides pure platinum electrodes, platinized titanium electrodes were investigated for the conversion of n‐hexanoic acid to n‐decane [28] . Qui et al [10] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that at extreme cell voltages above 20 V a yield of 64.7 % of n‐triacontane was obtained in a basic electrolyte (1.3 M KOH) and at a cell temperature of 55 °C. Besides pure platinum electrodes, platinized titanium electrodes were investigated for the conversion of n‐hexanoic acid to n‐decane [28] . Qui et al [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides pure platinum electrodes, platinized titanium electrodes were investigated for the conversion of n-hexanoic acid to n-decane. [28] Qui et al [10] demonstrated the catalytic activity of RuO 2 and IrO 2 thin films for the conversion of valeric acid. The two latter studies report promising activity and selectivity to both Kolbe and (non)-Kolbe products, while platinum (e. g. platinum foil) was revealed as the most effective electrode for Kolbe electrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These olefins include important monomers like propylene [12,13] or ethyl acrylate [3], whereas oxygenated products show promising applications in fuel design [4] or fine chemical industry [6]. While the general reaction con-ditions of (Non-)Kolbe electrolysis were thoroughly studied [7,8], current research focuses on the substrate scope [14,15], economical and ecologically improved anodes [3,16], and sophisticated reaction engineering like in situ product separation [3,9,10] or continuous processes [10,17,18]. The Non-Kolbe electrolysis of monomethyl succinic acid enables a sustainable pathway to methyl acrylate, which is used in textile industry.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches are known to convert carboxylic acids (e.g., levulinic acid, hexanoic acid) into longer-chain aliphatic compounds (fuels) or high-value organic chemicals, ,, but the carboxylic acids need to be produced and purified before electrochemical conversion. Electro-biorefinery concepts combine biological and electrochemical processes to facilitate the conversion of complex renewable feedstocks into high-value chemicals. ,, Long-chain alkanes, such as decane, obtained from the Kolbe reaction, are suitable transportation fuels, but they are not ideal substrates for the chemical industry, due to their lack of chemical functional groups . Therefore, other non-Kolbe products, such as alkenes are more desirable.…”
Section: Introductionmentioning
confidence: 99%